دور الحوكمة في تحسين الأداء المالي للمؤسسة - غنية عبيدي; شيماء رزقه; سعدية حساني; أسماء حموية (جامعة الوادي University Of Eloued, 2024)
تهدف هذه الدراسة إلى توضيح دور الحوكمة في تحسين الأداء العالي للمؤسسة برذلك من خلال التطرق إلى مجموعة من المفاهيم والمصطلحات المتعلقة بالحوكمة والأداء المالي، كما تم الاعتماد على المنهج الوصفي في الجانب النظري، والتحليلي في الجانب التطبيقي من خلال دراسة حالة التي تمت على مستوى مديرية توزيع الكهرباء والغاز الوادي خلال الفترة (2019 2020 2021) من خلال إجراء المقابلات وكذلك الوثائق المقدمة من طرف المؤسسة ، حيث تم تحليل الوضعية المالية للمؤسسة باستخدام مؤشرات التوازن المالي والنسب المالية . ومن خلال نتائج الدراسة المتوصل اليها أن هناك علاقة إيجابية بين البات حوكمة المؤسسات والأداء المالي This study aims to clarify the role of governance in improving financial performance by addressing a group of concepts related to govemance and financial performance It also refled on the descriptive approach in the theoretical aspect.and the analytical approach in the the applied aspect through a case stulied aspect through a case stulied aspect through a case stulled aspect through a case stulled aspect through a case stuled aspect through a case stulied aspect through a case stulled aspect through a case study that was conducted at the level of the Electricity distribution directorat, Valley gas during the period (2019-2020-2021), Through conducting Interviews as well as documents submitted by the corporation, where the financial position of the corporation was analyzed using financial balance indicators and financial ratios, Through the results of the study, it was concluded that there is a positive relationship between corporate governance mechanisms and financial performance.
مذكرة ماستر
Keywords: الحوكمة، مبادئ الحوكمة الأداء المالي، المؤشرات المالية.; govemanceprinciples; financial performance; financialindicators